2019
DOI: 10.3390/ijms20092135
|View full text |Cite
|
Sign up to set email alerts
|

HDAC5 Expression in Urothelial Carcinoma Cell Lines Inhibits Long-Term Proliferation but Can Promote Epithelial-to-Mesenchymal Transition

Abstract: Class I histone deacetylases (HDACs) generally promote cell proliferation and tumorigenesis, whereas class IIA HDACs like HDAC4 and HDAC5 may promote or impede cancer development in a tissue-dependent manner. In urothelial carcinoma (UC), HDAC5 is often downregulated. Accordingly, HDAC5 was weakly expressed in UC cell lines suggesting a possible tumor-suppressive function. We therefore characterized the effects of stable HDAC5 expression in four UC cell lines (RT112, VM-Cub-1, SW1710 and UM-UC-3) with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…An important addition to this review is the original article by Buckwalter et al [8] who have systematically investigated the expression of HDACs in cellular and animal model systems of bladder cancer, comparing their results with data from primary tumors. Both articles are complemented by an original investigation addressing the function of HDAC5 [9]. This further supports the conclusion that predominantly class I HDACs, like HDAC1 and HDAC2, drive proliferation and survival of urothelial carcinoma cells [7,10], whereas class IIA enzymes, like HDAC4 and HDAC5, usually impede tumor growth.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…An important addition to this review is the original article by Buckwalter et al [8] who have systematically investigated the expression of HDACs in cellular and animal model systems of bladder cancer, comparing their results with data from primary tumors. Both articles are complemented by an original investigation addressing the function of HDAC5 [9]. This further supports the conclusion that predominantly class I HDACs, like HDAC1 and HDAC2, drive proliferation and survival of urothelial carcinoma cells [7,10], whereas class IIA enzymes, like HDAC4 and HDAC5, usually impede tumor growth.…”
supporting
confidence: 55%
“…This further supports the conclusion that predominantly class I HDACs, like HDAC1 and HDAC2, drive proliferation and survival of urothelial carcinoma cells [7,10], whereas class IIA enzymes, like HDAC4 and HDAC5, usually impede tumor growth. Intriguingly, however, and in keeping with the ideas outlined by Monteiro-Reis et al [5], overexpression of HDAC5 induced EMT in one urothelial carcinoma cell line [9].…”
mentioning
confidence: 58%
“…As well, knockdown of HDAC5 by siRNA technology in glioma cells suppressed the doxorubicin-induced EMT 18 . Recently, Jaquva et al revealed that HDAC5 overexpression in multiple urothelial carcinoma (UC) cell lines decreased cell proliferation, however in VM-Cub-1 cell line HDAC5 overexpression induced a dramatic EMT change, with the weak effect of HDAC4 on cell phenotypes 19 . Taken together it is suggested that HDAC5 is a promising target to ameliorate diabetic kidney disease via regulating EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the wealth of knowledge regarding these enzymes, we have much to learn. For example, class I HDAC enzymes generally promote tumorigenesis, and class IIA may promote or impede cancer development; however it was only recently discovered that HDAC5 induced anti-proliferative or pro-EMT effects depending on the cell line in which it was overexpressed (154).…”
Section: Epigenetic Mechanisms Involved In Emt-room To Explorementioning
confidence: 99%